2021
DOI: 10.1186/s12884-021-04022-x
|View full text |Cite
|
Sign up to set email alerts
|

Health care workers’ perceptions of episiotomy in the era of respectful maternity care: a qualitative study of an obstetric training program in Mexico

Abstract: Background Episiotomy in Mexico is highly prevalent and often routine - performed in up to 95% of births to primiparous women. The WHO suggests that episiotomy be used in selective cases, with an expected prevalence of 15%. Training programs to date have been unsuccessful in changing this practice. This research aims to understand how and why this practice persists despite shifts in knowledge and attitudes facilitated by the implementation of an obstetric training program. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 52 publications
(46 reference statements)
3
12
1
Order By: Relevance
“…Similarly, the episiotomy rate in all vaginal deliveries in the United States fell from 60.9% in 1979 to 24.5% in 2004 ( 89 ), and the rate in Hong Kong fell from 73% in 2003 to 27% in 2008 ( 86 ). In contrast, the pooled estimate for episiotomy practice, in all vaginal deliveries, in this meta-analysis was lower than in a study conducted in India, where 63.4% ( 90 ), Oman, 66% ( 27 ), Portugal, 72.9% in 2010 ( 20 ), Mexico City, 77.2% ( 25 ), Turkey, 93.3% ( 91 ), Phnom Penh, Cambodia, 94.5% ( 28 ), and Taiwan, 100% ( 23 ), which may suggest liberal use in these countries.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Similarly, the episiotomy rate in all vaginal deliveries in the United States fell from 60.9% in 1979 to 24.5% in 2004 ( 89 ), and the rate in Hong Kong fell from 73% in 2003 to 27% in 2008 ( 86 ). In contrast, the pooled estimate for episiotomy practice, in all vaginal deliveries, in this meta-analysis was lower than in a study conducted in India, where 63.4% ( 90 ), Oman, 66% ( 27 ), Portugal, 72.9% in 2010 ( 20 ), Mexico City, 77.2% ( 25 ), Turkey, 93.3% ( 91 ), Phnom Penh, Cambodia, 94.5% ( 28 ), and Taiwan, 100% ( 23 ), which may suggest liberal use in these countries.…”
Section: Discussioncontrasting
confidence: 87%
“…Reported rates of episiotomies vary greatly from one country to another across the globe. The lowest rate (1%) of episiotomy was reported in Sweden, whereas the highest (100%) was reported in Taiwan among primiparous parturients (23) (20,(23)(24)(25)(26)(27)(28). In addition, significant number of women undergone episiotomy in Asian countries, 42-98% (23,29,30).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some studies have shown that fetal distress is one of the main reasons for performing an episiotomy 21 , which is consistent with several other findings 22,23,24 . In the Seijmonsbergen-Schermers et al study 21 , fetal macrosomia and other physical characteristics were criteria for performing episiotomy.…”
Section: Factors Related To the Fetussupporting
confidence: 87%
“…The literature review did not yield any studies that dealt with all the components of the 2018 WHO intrapartum care model. Moreover, few qualitative studies were conducted on this subject, most of which were not comprehensive and discussed only some components of this model such as respectful maternal care and continuity of care ( 22 24 ). In line with the population policies of the Iranian government and the promotion of intrapartum care, this study on the 2018 WHO intrapartum care model is expected to lead to an increase in women's positive experiences of labor and their desire for giving birth to another child through normal vaginal delivery and also to reduce the rate of unnecessary cesarean sections.…”
Section: Introductionmentioning
confidence: 99%